Multidimensional Poverty among the Villages of the South African Former Homeland of Qwaqwa - Nishimwe-Niyimbanira, Rachel (International Journal of Economics and Financial Issues, 2018)
Poverty has remained topical in international development policy efforts, particularly in the developing world. It is much more topical in the South Africa context due to the legacy left by the apartheid system. Keeping in mind the history of South Africa, this study aims to analyse the multidimensional aspects of poverty in different villages of the former South African homeland of QwaQwa. Seven dimensions of deprivation that could be constructed based on 18 indicators were identified. These dimensions include education, housing and clothing, water and sanitation, assets, air quality, income, and health. A sample of 404 households was randomly selected in eight villages of QwaQwa. The Alkire and Foster family of measures was used for the multidimensional analysis of poverty and was compared to the income poverty. The results showed that the village having the highest estimates of income headcount ratio H was not the one having the highest estimates of multidimensional headcount ratio and intensity of poverty M0. Similarly, the village with the lowest estimates of income H was not the one having the lowest estimates of multidimensional H and M0. This was due to the presence of high levels of deprivation in the other dimensions compared to the income deprivation. The intensity of poverty showed that Kudumane and Boitekong are the most deprived villages while Bochabela was found to be the least deprived village. The robustness of village rankings to changes in the poverty cut-off k confirmed that Kudumane and Boitekong are dominated by other villages both in poverty headcount ratio and intensity of poverty. The study has brought out meaningful results that can potentially provide useful tools for budget allocation among the villages of QwaQwa and within themselves, by applying among other things, the use of different dimensions. Keywords: Multidimensional poverty, former South African Homeland, Alkire and Foster methodology, QwaQwa JEL Classifications: I3, I32, O55